HUBUNGAN POWER OTOT TUNGKAI DAN KOORDINASI MATA-KAKI DENGAN KETERAMPILAN LONG PASSING SEPAK BOLA PEMAIN BONGAS RAYA FC - Sidah, Sidah; Mubarok, Mochamad Zakky (STKIP Melawi, 2024)
Abstract: This study aims to determine the relationship between leg muscle power and eye-foot coordination with the long passing skills of Bongas Raya Fc players. This study uses a correlational method where data obtained from the field is transformed into numbers so that statistical calculations can be carried out. The total population is less than 30 people with 18 Bongas Raya Fc players using saturated sampling techniques. The instruments in this study used three instruments, namely leg muscle power using the squat jump test, eye-foot coordination using the passing and stop passing test, and long passing using the long passing skill test. Based on the results of the study obtained. Power leg muscles and eye-foot coordination with long passing skills, conditions with significant description. The conclusion of this study is that there is a relationship between leg muscle power and eye-foot coordination together with the long passing skills of Bongas Raya Fc players with a strong level of relationship.Keywords: leg muscle power, eye-foot coordination, long passing, football. Abstrak: Penelitian ini bertujuan untuk mengetahui hubungan power otot tungkai dan koordinasi mata-kaki dengan keterampilan long passing pemain Bongas Raya Fc. Penelitian ini menggunakan metode korelasional dimana data-data yang diperoleh dari lapangan ditransformasikan ke dalam angka-angka sehingga dapat dilakukan perhitungan statistik. Jumlah populasi kurang dari 30 orang dengan sempel 18 pemain Bongas Raya Fc menggunakan teknik sampling jenuh. Instrumen dalam penelitian ini menggunakan tiga instrumen yaitu power otot tungkai menggunakan tes squat jump, koordinasi mata-kaki menggunakan tes passing dan stop passing, dan long passing menggunakan tes keterampilan long passing. Berdasarkan hasil penelitian didapatkan. Power otot tungkai dan koordinasi mata-kaki dengan keterampilan long passing, kondisi dengan keterangan signifikan. Kesimpulan penelitian ini yaitu terdapat hubungan power otot tungkai dan koordinasi mata-kaki secara bersama-sama dengan keterampilan long passing sepak bola pemain Bongas Raya Fc dengan tingkat hubungan kuat.Kata kunci: power otot tungkai, koordinasi mata-kaki, long passing, sepakbola.